Cryptocurrency as a Means of Gratification: A Comparative Analysis of Conventional and Digital Gratification in Islamic Criminal Law - Priyono, Erwan Adi; Handayani, I Gusti Ayu Ketut Rachmi; Rustamaji, Muhammad; Fernando, Zico Junius; Arifin, Firdaus (al-'adalah, 2026)
This study investigates whether cryptocurrency-based gratification can be legally classified as risywah under Islamic criminal law and analyzes how its characteristics differ from those of conventional gratification. Employing a normative legal research methodology, the study utilizes statutory, conceptual, comparative, and prescriptive approaches. The statutory approach involves examining anti-corruption norms, Islamic criminal law principles, contemporary fatwas, and legal doctrines related to bribery and digital assets. The conceptual approach assesses cryptocurrency as māl and as an object of unlawful benefit, while the comparative approach evaluates conventional and digital gratification in terms of object, transfer mechanism, concealment pattern, evidentiary challenges, and legal consequences. Legal content analysis is conducted by interpreting classical fiqh doctrines, qawā‘id fiqhiyyah, and maqāṣid al-sharī‘ah in the context of contemporary crypto-based transactions. The findings indicate that cryptocurrency gratification meets the substantive elements of risywah when it possesses economic value, is provided to influence public authority or judicial decision-making, and results in unfair advantage, even if transferred through intangible and decentralized digital mechanisms. The primary distinction between conventional and digital gratification lies in technological form, anonymity, cross-border nature, and evidentiary complexity, rather than legal nature. Consequently, crypto-based gratification should be treated as equivalent to conventional bribery under Islamic criminal law, based on the principle that legal consideration is determined by substance rather than form. The study contributes by proposing a functional-equivalence model of risywah that extends classical Islamic criminal law to digital gratification, thereby enhancing the relevance of fiqh jināyah in addressing corruption in the blockchain era.